2019
DOI: 10.3390/biology9010004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Beclin 1-Dependent Autophagy in Cancer

Abstract: Autophagy (self-eating) is an intracellular degradation process used by cells to keep a "clean house"; as it degrades abnormal or damaged proteins and organelles, it helps to fight infections and also provides energy in times of fasting or exercising. Autophagy also plays a role in cancer, although its precise function in each cancer type is still obscure, and whether autophagy plays a protecting (through the clearing of damaged organelles and protein aggregates and preventing DNA damage) or a promoting (by fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 97 publications
(123 reference statements)
1
60
0
1
Order By: Relevance
“…Moreover, Beclin 1 is often reduced in BCs including TNBC, and this could have adverse effects on cancer growth [167,168]. Indeed, the inducer regulatory role of Beclin 1 in the autophagic flux in MCF-7 cells has been linked with cellular proliferation slowdown [169].…”
Section: Rutheniummentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Beclin 1 is often reduced in BCs including TNBC, and this could have adverse effects on cancer growth [167,168]. Indeed, the inducer regulatory role of Beclin 1 in the autophagic flux in MCF-7 cells has been linked with cellular proliferation slowdown [169].…”
Section: Rutheniummentioning
confidence: 99%
“…In support of these findings, a few recent data show autophagic machinery defects next to Beclin 1 lack under different circumstances, as well as chemotherapeutic interventions. Moreover, Beclin 1 is often reduced in BCs including TNBC, and this could have adverse effects on cancer growth [ 167 , 168 ]. Indeed, the inducer regulatory role of Beclin 1 in the autophagic flux in MCF-7 cells has been linked with cellular proliferation slowdown [ 169 ].…”
Section: Biological Responses To Nucleolipid Ru-based Nanoformulamentioning
confidence: 99%
“…Multiple Beclin 1 phosphorylation events have been reported that eventually modulate autophagy activity in mammals, either by induction or inhibition (reviewed in [30,31]), and multiple oncogenic kinases have also been involved in autophagy modulation through Beclin 1 phosphorylation [32]. Phosphorylation at Ser90 has been shown to activate autophagy through several kinases, including MK2/3 [15], DAPK3, [33], calcium-calmodulin-dependent protein kinase type II (CAMKII, [34]), AMP-activated protein kinase (AMPK, [35]), and also by the phosphatase PP2A [33].…”
Section: Beclin 1 Regulation By Tyrosine Phosphorylationmentioning
confidence: 99%
“…Although human cancers largely lack evidence of genetic inactivation of core autophagy machinery, various murine models have revealed that knockouts of key autophagic genes promote tumorigenesis ( Amaravadi et al, 2016 ). In addition to its role in initiating autophagy ( Vega-Rubín-de-Celis, 2019 ), BECN1 is essential for early embryonic development and regulates growth factor receptor signaling ( Yue et al, 2003 ; Rohatgi and Shaw, 2016 ). As a result, biallelic deletions of BECN1 cannot be studied because of lethality in animal models.…”
Section: Autophagy and Cancermentioning
confidence: 99%